The thalamic regulation of striatal function in normal and Parkinsonian states - Smith, Yoland (Henry Stewart Talks, 2014)
Anatomy, physiology and pathophysiology of the thalamostriatal system in Parkinson’s disease, Thalamostriatal network connectivity, electrophysiological properties and potential role in cognitive functions, Degeneration of the thalamostriatal system and its impact upon the development of early cognitive deficits in Parkinson’s disease.
Reviewed at 2020/10/14